Self-Efficacy and Emotion Regulation as Correlates of Psychological Distress among Family Caregivers of Working-Age Hemodialysis Patients in Indonesia: A Cross-Sectional Study - Supriati, Lilik; Sunarto, Muhammad; Nova, Renny; Kapti, Rinik Eko; Rismayanti, I Dewa Ayu (Chakra Brahmanda Lentera Institute, 2026)
Background: The increasing prevalence of chronic kidney disease among working-age populations has heightened psychological distress among family caregivers, especially in low- and middle-income countries. However, the roles of self-efficacy and emotion regulation in influencing this distress remain unclear. This study aimed to examine the relationships between self-efficacy, emotion regulation, and psychological distress among family caregivers of patients undergoing hemodialysis. Methods: This cross-sectional study, reported in accordance with STROBE guidelines, involved 201 family caregivers recruited through convenience sampling to ensure accessibility in hemodialysis settings. Self-efficacy and emotion regulation were independent variables, while psychological distress was the dependent variable. Data were collected using validated and reliable instruments General Self Efficacy Scale (GSE), Emotion Regulation Questionnaire (ERQ), The Kessler Psychological Distress and analyzed using Spearman’s rank correlation tests. Results: The results show significant negative correlations between psychological distress and both self-efficacy (r = −0.346, p < 0.001) and emotion regulation (r = −0.217, p < 0.001). These findings indicate that higher levels of self-efficacy are associated with lower psychological distress. Similarly, better emotion regulation is associated with reduced psychological distress, with self-efficacy demonstrating a stronger association. Conclusion: These findings highlight the importance of psychosocial resources in supporting caregiver well-being in family-centered care contexts. It is recommended to integrate psychological counseling programs for families of patients with chronic kidney disease undergoing hemodialysis, along with structured educational interventions emphasizing the importance of emotion management.